Gene therapy and gene transfer: vector integration preferences and integration site analysis - Bushman, Frederic (Henry Stewart Talks, 2014)
Introduction: human gene therapy with integrating vectors, Methods for monitoring gene transfer, HIV integration targeting, Gammaretroviral integration targeting, Analysis of vector integration in human gene therapy